A Framework for Analyzing Broadly Engaged Philosophy of Science. Issue 2 (October 2021) - Plaisance, Kathryn S.; Elliott, Kevin C.
Abstract : Philosophers of science are increasingly interested in engaging with scientific communities, policy makers, and members of the public; however, the nature of this engagement has not been systematically examined. Instead of delineating a specific kind of engaged philosophy of science, as previous accounts have done, this article draws on literature from outside the discipline to develop a framework for analyzing different forms of broadly engaged philosophy of science according to two key dimensions: social interaction and epistemic integration. Clarifying the many forms of engagement available to philosophers of science can advance future scholarship on engagement and promote more strategic engagement efforts.